Eine Deregulierung der Ladenöffnungszeiten hätte auch in Bayern zu mehr Beschäftigung im Lebensmitteleinzelhandel geführt - Bossler, Mario; Oberfichtner, Michael; Pyka, Vinzenz (IAB-Forum, 2020)
Während die meisten Bundesländer ihre Ladenöffnungszeiten liberalisiert haben, hält Bayern bislang an seinen restriktiveren Regelungen fest. Aus diesem Grund hat sich die Zahl der Beschäftigten im Lebensmitteleinzelhandel dort weniger positiv entwickelt als in vergleichbaren Bundesländern

Unionization of retired workers in Europe - Pyka, Vinzenz; Schnabel, Claus (European Journal of Industrial Relations, 2024)
We shed light on an understudied group: retirees in unions. Using representative individual-level data of 19 European countries, we find that the share of retirees in unions and the union density of retirees increased between 2008 and 2020. Econometric analyses indicate that on average retired workers’ probability of union membership is 17 percentage points lower than that of active workers, with some variation among countries. This finding is consistent with social custom models and cost–benefit considerations, but it partly questions the inter-generational solidarity model put forward in the literature. We further find that some determinants of union membership differ between active and retired workers; for instance, the (former) status of being a full-time or blue-collar worker is only statistically significant for active but not for retired workers. Overall, standard membership models better explain the unionization of active than retired workers.
CRIS-Team Scopus Importer:2024-06-07
Keywords: Europe; J26; J51; retirement; Trade union; union membership